Evaluation of Drug Utilization and Dose Intensity Pattern in Dyslipidemic Patients with Type 2 Diabetes Mellitus - Safwan, Abdul; G., Suresh; Shaji, Bipin; Sridhar, Srinitha; Kolar, Reshma; Joel, Juno Jerold (Journal of Health and Allied Sciences NU, 2023)
Dyslipidemia can increase the risk of cardiovascular disease in individuals with metabolic diseases. Patients may have to take multiple medications simultaneously, leading to polypharmacy. A retrospective study was conducted to evaluate drug utilization and dose intensity patterns in dyslipidemic patients with type 2 diabetes mellitus over an 8-month period at a tertiary care hospital. The study included the case sheets of patients diagnosed with dyslipidemia and type 2 diabetes. The required data for the study were collected from the patient's case sheets from the Medical Records Department (from June 2015 to May 2020). The data were documented using MS Excel 2013 and analyzed descriptively using SPSS software version 20. Among the 384 study population, 53% were males and 47% were females, with an age group of 45 to 59 years. Metformin and glimepiride were the most commonly prescribed oral hypoglycemic agents, while glibenclamide was the least prescribed. Atorvastatin was the most prescribed hypolipidemic agent. The combination of atorvastatin and fenofibrate was the most preferred combination therapy. The most frequently prescribed hypoglycemic and hypolipidemic agents were metformin and atorvastatin, respectively. Dyslipidemic patients with diabetes mellitus require the administration of multiple medications. It is crucial to monitor medication adherence and medication-related problems among these populations.
Keywords: drug utilization; dyslipidemia; type 2 diabetes mellitus; medication adherence